Pengaruh Kompetensi, Motivasi, Pengharapan Terhadap Kinerja Pegawai di Rumah Sakit Wisata Indonesia Timur - Achmad Hilal (Journal of Health Quality Development, 2022)
Hospital employee competence is an absolute requirement that must be owned by hospital organizations as an absolute requirement in the current era of competition. In addition, the motivation and expectations of employees become basic needs that support employees so that human resources fulfill their competencies, this study is aimed at looking at the effect of motivation on employee competence at tourist hospitals in eastern Indonesia. The method used is descriptive quantitative by using a frequency table to describe employee perceptions of the proposed indicator components. The results showed that the competence, motivation and expectations of employees had a significant effect on employee performance at the Eastern Indonesia Tourism Hospital. The improvement of employee competence is carried out through increasing skills, knowledge, providing guidance/direction by the leadership; When employee motivation is growing, it will encourage an increase in their performance; When employees expect various things related to work and organizational conditions, the implementation of work will be more focused with satisfactory work results.